Desenvolvimento e avaliação da influência das vacinas de células dendríticas e células NK em modelo experimental induzido ao câncer de mama com células 4T1 - ALVES, Eduardo Arthur Rodovalho (2020)
Introduction: Immunotherapies have become a focus in the treatment of several types of cancer, mainly for breast cancer. The relevance of using it as a treatment is done through the stimulation of cells of the immune system to recognize tumor antigens, generating specific immune responses directed against these cells, preventing tumor progression. Objectives: In order to evaluate the treatment against breast cancer induced with 4T1 cells, in Balb / C mice, we used the immunization protocol with dendritic cell (DC) vaccines and Natural Killer (NK) cells. Materials and Methods: The study comprised mice from the control group, untreated tumor, tumor treated with DC cell vaccine and the tumor group treated with NK cell vaccine, the treatment protocol was carried out for 3 weeks, at the end of which they were submitted to euthanasia to remove the spleen and tumor infiltrate. The biological material was prepared for flow cytometry using the cell activation markers NK, NKG2D, NKp46 and Ly49G2, NKG2A/C/E inhibition, associated with each one of the markers for cytokines, IL-10, IL-2 , IL-12, IL-17, IFN-γ and TNF-α. Results: The results demonstrated that the NK cells in the face of immunotherapy with DC cells, directly influenced the antitumor response, since we observed greater expression of the activation receptors NKp46 and NKG2D, and less expression of the inhibitors of Ly49G2 and NKG2A/C/E, with the production of cytokines IL-2, IL-10, IFN-γ, TNF-α and IL-12, inducing the activation of NK cells and promoting the activation of other cells of the immune system. For treatment with the NK cell vaccine, our findings show an imbalance in the expression of activation and inhibition receptors, where a high expression of inhibitory receptors such as Ly49G2 leads to an interference in the elimination of target cells with low expression of MHC class I. Conclusions: Concluding our findings, we demonstrate that immunotherapy with DC is able to alter the profile of NK cells, directly influencing the antitumor response, due to the reduced expression of the inhibitor receptor and the increase in the production of cytokines such as TNF-α and IFN- γ stimulating the immune system to eliminate tumor cells, however, in immunotherapy with NK cells the increased expression of the Ly49G2 inhibitory receptor, and the migration of this phenotypic profile to the tumor microenvironment, prevents NK cells from being activated in association with the presence of IL -10, generating a state of numbness and contributing to the progression of the tumor.